Highly Sensitive Ratiometric Fluorescent Probe for the Detection of Mercury Ions - Y. Yue; Z. Gao; L. Chen; R. Su; W. Qi; Z. He (Chemical Engineering Transactions, 2017)
An effective dual-emission fluorescent probe combining gold nanoclusters (AuNCs) and carbon dots (CDs) was fabricated for the detection of mercury ions (Hg2+). CDs doped into silica nanoparticles exhibited a reference fluorescence signal, while the outer AuNCs layer stabilized by bovine serum albumin (BSA) was extremely sensitive to Hg2+. This probe selectively detected Hg2+ in a good linear range from 0.43 to 39 μM and a detection limit (signal-to-noise ratio is 3) of 81 nM. The increase in the Hg2+ concentration was accompanied by the colour change from reddish violet to blue. This method exhibited several advantages of facile preparation and operation and high selectivity and sensitivity. This dual-emission fluorescent probe has significant potential for the ‘‘naked eye’’ detection of Hg2+.